The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1021/acs.jpclett.2c02177
|View full text |Cite
|
Sign up to set email alerts
|

Defect Regulation of Terbium-Doped Y2Zr2O7 Transparent Ceramic for Wide-Range Multimode Tunable Light-Shielding Windows

Abstract: In the most promising new window materials, the light-blocking property of the state-of-the-art transparent polycrystalline ceramics is still located in the UV range, which undoubtedly limits their applications. Herein, a transparent Y 2 Zr 2 O 7 :Tb (YZO:Tb) ceramic for light-shielding windows was prepared by a solid-state reaction and vacuum sintering method. Two simple and efficient routes, with doping concentrations varying and air-annealing temperatures regulating, were developed for the first time to con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 42 publications
(61 reference statements)
0
16
0
Order By: Relevance
“…intrinsic absorption of Pr 3+ . However, these YZO:Pr ceramics were sintered in the vacuum environment, some oxygen vacancies (Vö) and free electrons (e′) have been created owing to the oxygen partial difference between the ceramic and the sintering furnace, thereby promoted the generation of some F + and F defect centers that can capture some photons [32,37]. Thus, as shown in Fig.…”
Section: Optical Transmission and Photoluminescencementioning
confidence: 99%
See 1 more Smart Citation
“…intrinsic absorption of Pr 3+ . However, these YZO:Pr ceramics were sintered in the vacuum environment, some oxygen vacancies (Vö) and free electrons (e′) have been created owing to the oxygen partial difference between the ceramic and the sintering furnace, thereby promoted the generation of some F + and F defect centers that can capture some photons [32,37]. Thus, as shown in Fig.…”
Section: Optical Transmission and Photoluminescencementioning
confidence: 99%
“…and [𝑃𝑃𝑃𝑃 𝐿𝐿𝐿𝐿 4 + -𝑒𝑒 ′ ] during high-temperature air annealing [30][31][32], quenching photoluminescence, which undoubtedly limits their optical applications. Fortunately, in our recent report [31,32], when YZO ceramics are sintered in a vacuum oxygen-deficient environment, some oxygen vacancies (Vö) and free electrons (e') will be generated due to the oxygen partial difference between the ceramic and the sintering furnace. Therefore, some tetravalent ions in the ceramic body could trap an e' become trivalent state via appropriate vacuum re-annealing after air annealing.…”
Section: Introductionmentioning
confidence: 99%
“…To add to these, they have higher melting point, high chemical and physical stability, and high near-infrared, heat, and radiation reflectivity and can be explored as new heat insulating materials with low thermal conductivity . Defects in YZO have been harnessed in many applications such as sensitized fluorescence, light shielding windows, thermographic phosphors, solid oxide fuel cells, and smart acoustic absorption windows. Despite these potential applications, there are absolutely no reports at all wherein its usability as a gas sensor has been tested despite few reports on the same using other pyrochlores. Shimizu and Maeda reported the pyrochlore-type oxide for NO x gas sensing, whereas Raauf et al reported the Nd 2 Sn 2 O 7 system for the detection of hydrogen gas.…”
Section: Introductionmentioning
confidence: 99%
“…However, the conventional Dy‐based composite luminescence converters fabricated by embedding phosphor powders in organic binders with poor chemical, thermal, and optical stability, which limited their further development in high‐power, high‐brightness solid‐state lighting 4,8,10 . As an alternative, some Dy‐doped glass converters have been developed, but the poor physical and chemical stabilities of the glass–ceramics make them unsuitable to be served in some harsh cases 11,12 . To address these shortcomings, researchers have been working on developing innovative light‐emitting converter materials with the potential for extreme environmental use, among which the polycrystalline ceramic phosphors are becoming a promising candidate due to their good optical transparency, high strength, corrosion and high‐temperature resistance, and so on 13–16 …”
Section: Introductionmentioning
confidence: 99%
“…4,8,10 As an alternative, some Dy-doped glass converters have been developed, but the poor physical and chemical stabilities of the glass-ceramics make them unsuitable to be served in some harsh cases. 11,12 To address these shortcomings, researchers have been working on developing innovative light-emitting converter materials with the potential for extreme environmental use, among which the polycrystalline ceramic phosphors are becoming a promising candidate due to their good optical transparency, high strength, corrosion and high-temperature resistance, and so on. [13][14][15][16] Usually, the luminescence properties of doped active ions are closely related to the corresponding host material.…”
Section: Introductionmentioning
confidence: 99%